Investigation Of Antimutagenic Activities of Commiphora Gileadensis Essential Oil Against Cyclophosphamide Induced Genotoxicity in Mice - Salman, Asmaa S.; Alsherif , Emad A. (International Journal of Halal Research, 2023)
Commiphora gileadensis, a wild aromatic medicinal plant, is part of the Burseraceae family, which contains 190 species under the genus Commiphora. It has both ethnobotanical and therapeutic applications. Currently, the antigenotoxic effects of Commiphora gileadensis essential oil (CEO) was investigated by assessing chromosomal anomalies in bone marrow cells, DNA fragmentation in hepatocytes, chromosomal aberrations in spermatocytes, and sperm head and tail anomalies in mice. Animals were divided into the following groups: CP treated groups (20 mg /kg b.w.), the control group (received no treatment), corn oil treated group, group administered CEO for 7 days at 300 mg /kg b.w., three groups administered CEO for 7 days at (100, 200 or 300 mg /kg b.w.) plus cyclophosphamide. In vivo investigations demonstrated that preliminary treatment with the tested concentrations of CEO reduced CP-induced injury. Therefore, research has shown that the CEO is a potential factor for protection against the genetic toxicity caused by CP.